Management and Health Risks of Mineral Mining Workers (Nickel) - Faisal Reza; Savitri Citra; Achmad Achmad; Endy Novryan Ridwan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nickel mining in Southeast Sulawesi, Indonesia, is a vital economic sector but poses high health risks to workers due to exposure to nickel dust, noise, and heavy working conditions, leading to diseases such as silicosis and high rates of occupational accidents. This study aims to identify the health risks of nickel mine workers, evaluate the occupational safety and health (OHS) system, and formulate a mitigation plan to improve worker welfare and operational sustainability. Using a qualitative approach with quantitative descriptive elements at the Kolaka Regency mine, data were collected through observation, interviews, environmental measurements (dust, noise, vibration, lighting), and secondary analysis on high-risk workers (working period ≥6 months) with purposive sampling. Thematic and descriptive analyses were conducted with triangulation for validity. The results showed health risks from physical (noise 88.6 dB, extreme temperatures, vibration), chemical (nickel dust, silica), biological (infection), ergonomic (work posture), and psychosocial (stress) hazards, with clinic visits (3,792 cases) dominated by flu (34%), dyspepsia (12%), and fever (11%). New workers (0–2 years, 43%) and 30–39 years old (40%) are most vulnerable. OHS management includes risk identification (IBPR), health checks, clinics, training, and environmental monitoring, with respirable dust (0.025–0.393 mg/m³) and vibration (<1.2249 m/s²) below TLV, but low noise and lighting (5 lux) require PPE and additional lighting. Wet preparation ergonomics (score 8, >TLV) require administrative control. In conclusion, strengthening HRA, routine environmental monitoring, use of PPE, improving lighting, ergonomics, OHS training, and psychological support for new workers, as well as periodic health data analysis, can reduce health risks, support worker welfare, and safemine operations. Keywords: nickel mining, health risks, OHS, health management, Southeast Sulawesi.